Delineation of Apathy Subgroups in Parkinson's Disease: Differences in Clinical Presentation, Functional Ability, Health‐related Quality of Life, and Caregiver Burden. Issue 1 (10th December 2020) - Eglit, Graham M.L.; Lopez, Francesca; Schiehser, Dawn M.; Pirogovsky‐Turk, Eva; Litvan, Irene; Lessig, Stephanie; Filoteo, J. Vincent
Abstract: Background: Apathy is a prevalent, multidimensional neuropsychiatric condition in Parkinson's disease (PD). Several authors have proposed apathy subtypes in PD, but no study has examined the classification of PD patients into distinct apathy subtypes, nor has any study examined the clinical utility of doing so. Objectives: The current study used a data‐driven approach to explore the existence and associated clinical characteristics of apathy subtypes in PD. Method: The Apathy Scale (AS) was administered to 157 non‐demented individuals with PD. Participants were classified into apathy subgroups through cluster analysis. Differences among apathy subtypes on external clinical indicators were explored across apathy subgroups. Results: Individuals with PD were classified into three subgroups: a Non‐Apathetic group with low levels of apathy symptoms, a Low Interest/Energy group, characterized by elevated symptoms of low interest/energy and minimal low initiation/emotional indifference symptoms, and a Low Initiation group, characterized by an absence of low interest/energy symptoms and elevated levels of low initiation/emotional indifference symptoms. Both Low Interest/Energy and Low Initiation groups exhibited worse depression, fatigue, anxiety, health‐related quality of life, and caregiver burden than the Non‐Apathetic subgroup. The Low Initiation group exhibited worse overall cognition, emotional well‐being, state anxiety, communicative ability, and functional ability than the Low Interest/Energy group. Importantly, disease‐related characteristics did not differ across apathy symptom subgroups. Conclusions: Non‐demented PD patients can be separated into distinct apathy symptom subgroups, which are differentially associated with important clinical variables. Apathy subgroup membership may reflect disruption to different neural systems independent of disease progression.